The Influence of E-Samsat, Tax Sanctions, Tax Socialization, and Tax Amnesty on Motor Vehicle Tax Compliance in Denpasar City - Ildefonsus Zuanda Dunas; Gusti Ayu Putu Eka Dewi Prihantari (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of the E-Samsat system, tax sanctions, tax socialization, and tax amnesty programs on motor vehicle tax compliance in Denpasar City. The background of this research lies in the increasing number of registered motor vehicles in Bali, which has not been followed by proportional growth in tax revenues, as evidenced by the rising number of arrears between 2020 and 2023. This phenomenon raises questions about taxpayers’ compliance and the effectiveness of existing government policies. A quantitative approach was employed, grounded in attribution theory as the theoretical framework to explain how external factors may shape taxpayer behavior. Primary data were collected through structured questionnaires distributed to 100 respondents at the Denpasar SAMSAT Office, using an accidental sampling method. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25, preceded by validity, reliability, and classical assumption tests to ensure the robustness of the findings. The results indicate that both the E-Samsat system and tax sanctions have a significant and positive effect on taxpayer compliance, highlighting the importance of accessible digital services and strict law enforcement in encouraging tax payment. In contrast, tax socialization and tax amnesty programs do not show a significant effect on motor vehicle tax compliance. This suggests that socialization efforts have yet to be optimally delivered and that amnesty policies may only provide short-term relief without fostering sustainable compliance. These findings provide practical implications for local governments in designing policies to enhance compliance. Strengthening digital tax systems such as E-Samsat, improving service quality, and enforcing effective sanctions should remain top priorities. Meanwhile, tax socialization programs should be redesigned to be more engaging and targeted, and the long-term consequences of tax amnesty should be carefully considered.